Predisposing Factors Related to Four ANC Visits (K4) on TM III Pregnant Women at Danurejan I Primary Health Center of Yogyakarta - Yulyani, Linda; Daryanti, Menik Sri (GHMJ (Global Health Management Journal), 2020)
Pregnancy may cause problems or become a complication at any time. However, complications of pregnancy and childbirth can be prevented by regular antenatal care (ANC) visits. Four ANC visits (K4) are indicators used to assess the quality of health services for pregnant women. Four ANC visits (K4) are also the indicators to see the frequency that refers to the trimester period when conducting a pregnancy check. Nationally, performance indicators for the coverage of four ANC visits (K4) on pregnant women in 2014 did not reach the target. There are various factors that may contribute to an unsuccessful four ANC visit (K4) of pregnant women that come from predisposing, enabling and reinforcing factors. The objective of the study is to investigate the correlation between maternal age and four ANC visits (K4) on TM III (trimester III) pregnant women at Danurejan I Primary Health Center of Yogyakarta. It is an analytic observational study design with cross-sectional approach. The sample was taken by accidental sampling technique with the inclusion and exclusion criteria as many as 30 TM III pregnant women. The result of this study shows that from four factors that analyzed, only two factors have a significant relationship with four ANC Visits (K4), which are maternal age (pv=0.000) and parity (pv=0.000). Meanwhile, education level (pv=0.155) and occupation (pv=0.210) have no correlation with four ANC Visits K4). Therefore, it can be concluded from this study that the maternal age and parity are the predisposing factors related to the four ANC Visits (K4). As a result, it is clear that promotion and prevention efforts such as health education about mature age at marriage and improving family planning programs are essential to increase four ANC Visits (K4). Future studies are expected to be conducted on larger sample sizes and different epidemiological approaches.